Positive electrode active material, method for manufacturing the same, positive electrode sheet, battery, and electric device

CN120657066BActive Publication Date: 2026-10-16CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410281498.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-03-11
Publication Date
2026-10-16
Estimated Expiration
2044-03-11

AI Technical Summary

Technical Problem

然而,钠电池的电化学性能不佳,导致其在实际应用中受到限制

Benefits of technology

[0003] The purpose of this application is to provide a positive electrode active material and its preparation method, a positive electrode sheet, a battery, and an electrical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120657066B_ABST
    Figure CN120657066B_ABST
Patent Text Reader

Abstract

The application provides a positive electrode active material, a preparation method of the positive electrode active material, a positive electrode sheet, a battery and an electric device. The positive electrode active material comprises a base body, and at least part of the surface of the base body has a coating layer; wherein the base body comprises Na y Ni a Mn b Fe c X d O 2+δ , X comprises one or more of Zn, Cu and Co, 0.8≤y≤1, 0.22≤a≤0.45, 0.33≤b≤0.45, 0.2≤c≤0.35, 0 The coating layer comprises a perovskite, and the perovskite comprises ABO3, A comprises one or more of Ca, La, Sr, Al, Gd and Y, and B comprises one or more of Ni, Mn, Fe and X. In this way, the gas production of the battery is reduced, and the cycle stability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of battery technology, specifically relating to positive electrode active materials and their preparation methods, positive electrode sheets, batteries, and electrical devices. Background Technology

[0002] Sodium-ion batteries, as a representative of rechargeable batteries, have been applied in various fields such as energy storage power systems (e.g., hydropower, thermal power, wind power, and solar power plants), electric vehicles, and aerospace. Compared to lithium-ion batteries, sodium-ion batteries have a cost advantage in raw materials, especially since sodium salts, the main component of the positive electrode active material, are more abundant and their price is much lower than that of lithium salts used in the positive electrode active material of lithium-ion batteries. This makes the cost of sodium-ion battery positive electrode active materials lower than that of lithium-ion batteries. However, the poor electrochemical performance of sodium-ion batteries limits their practical applications. Summary of the Invention

[0003] The purpose of this application is to provide a positive electrode active material and its preparation method, a positive electrode sheet, a battery, and an electrical device.

[0004] A first aspect of this application provides a positive electrode active material, the positive electrode active material comprising a matrix, wherein at least a portion of the surface of the matrix has a coating layer; wherein the matrix comprises Na y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, with 0.8 ≤ y ≤ 1, 0.22 ≤ a ≤ 0.45, 0.33 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.35, 0 < d ≤ 0.15, a + b + c + d = 1, and -0.1 ≤ δ ≤ 1. The coating layer includes perovskite, which includes ABO3, where A includes one or more of Ca, La, Sr, Al, Gd, and Y, and B includes one or more of Ni, Mn, Fe, and X. Therefore, at least a portion of the surface of the positive electrode active material substrate has a coating layer. This coating layer can reduce the probability of gas generation due to side reactions between the substrate and the electrolyte. Even if oxygen evolution occurs on the substrate surface, the perovskite structure of the coating layer contains oxygen vacancies, which can capture oxygen atoms, reducing the probability of oxygen atoms on the substrate surface combining to form oxygen gas, thereby reducing gas generation in the battery and improving the cycle stability of the battery.

[0005] According to some embodiments of this application, a transition layer is further included between the substrate and the coating layer, the transition layer comprising Na doped with the ABO3. y Ni a Mn b Fe c X d O2+δ This results in a better match between the lattice constants of the substrate and the transition layer, and between the transition layer and the cladding layer, thereby improving the structural stability of the cladding layer during cycling.

[0006] According to some embodiments of this application, the thickness ratio of the transition layer to the coating layer is 1:(10-50). Thus, the transition layer simultaneously includes elements A and B, as well as the material forming the matrix. The transition layer can act as a "support," reducing the volume change of the material during charging and discharging, and minimizing the impact on the electrode structure.

[0007] According to some embodiments of this application, the molar ratio of Na atoms to A atoms in the positive electrode active material is 1:(0.005-0.02). This results in the formation of a uniform coating layer on the surface of the substrate while increasing the substrate content in the positive electrode active material, thereby reducing battery gas production and increasing the battery's energy density.

[0008] According to some embodiments of this application, in the perovskite, A includes Ca and La, and the molar ratio of Ca atoms to La atoms is 0.25-4. This is beneficial for valence equilibrium and improves the structural stability of the perovskite.

[0009] According to some embodiments of this application, the volume average particle size D of the positive electrode active material V The particle size of the positive electrode active material is 3μm-10μm. Therefore, the smaller volume-average particle size reduces the migration path of sodium ions and improves the rate performance of the battery.

[0010] A second aspect of this application provides a method for preparing a positive electrode active material, comprising: mixing a positive electrode active material matrix with an A source, and performing a first sintering to cause the A source to react with at least a portion of the surface of the positive electrode active material matrix to form a coating layer comprising perovskite; the matrix comprising Na y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, with 0.8 ≤ y ≤ 1, 0.22 ≤ a ≤ 0.45, 0.33 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.35, 0 < d ≤ 0.15, a + b + c + d = 1, and -0.1 ≤ δ ≤ 1; the perovskite includes ABO3, A includes one or more of Ca, La, Sr, Al, Gd, and Y, and B is the Na in the reaction. y Ni a Mn b Fe c X d O 2+δThe provided metallic element includes one or more of Ni, Mn, Fe, and X. Therefore, the positive electrode active material prepared by this method possesses all the characteristics and advantages of the aforementioned positive electrode active materials, which will not be repeated here. In general, perovskite can be formed in situ on at least a portion of the substrate surface, reducing battery gas production under high pressure conditions and improving battery cycle stability.

[0011] According to some embodiments of this application, the A source includes one or more of a calcium source and a lanthanum source. This is beneficial for valence equilibrium and improves the structural stability of the perovskite.

[0012] According to some embodiments of this application, the calcium source includes one or more of calcium oxide, calcium carbonate, calcium hydroxide, calcium nitrate, calcium chloride, and calcium sulfate; the lanthanum source includes one or more of lanthanum oxide, lanthanum hydroxide, lanthanum nitrate, and lanthanum chloride.

[0013] According to some embodiments of this application, the A source includes a calcium source and a lanthanum source, and the molar ratio of the calcium source and the lanthanum source, calculated as Ca and La, is 0.25-4. This is beneficial for the valence equilibrium of the formed perovskite, improving the structural stability of the perovskite.

[0014] According to some embodiments of this application, the molar ratio of the matrix (calculated as Na) to the A source is 1:(0.005-0.02). This results in the formation of a uniform coating layer on the surface of the matrix while increasing the matrix content in the positive electrode active material, thereby reducing battery gas production and increasing the battery's energy density.

[0015] According to some embodiments of this application, the method satisfies one or more of the following conditions: the temperature of the first sintering is 400℃-1000℃, and the time of the first sintering is 2h-24h; the temperature of the second sintering is 700℃-1000℃, and the time of the second sintering is 6h-15h.

[0016] According to some embodiments of this application, the method satisfies one or more of the following conditions: the temperature of the first sintering is 600℃-900℃, and the time of the first sintering is 4h-18h; the temperature of the second sintering is 720℃-850℃, and the time of the second sintering is 7h-10h.

[0017] Therefore, by keeping the first sintering temperature within the above range, a uniform coating layer can be formed on the surface of the substrate while reducing the risk of sodium precipitation in the substrate; by keeping the second sintering temperature and time within the above range, the content of the substrate in the positive electrode active material can be increased, thereby increasing the specific capacity of the positive electrode active material.

[0018] The third aspect of this application provides a positive electrode sheet, including the positive active material provided in the first aspect of this application or the positive active material prepared by the method provided in the second aspect of this application.

[0019] The fourth aspect of this application provides a battery including the positive electrode provided in the third aspect of this application.

[0020] The fifth aspect of this application provides an electrical device, including the battery provided in the fourth aspect of this application.

[0021] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Attached Figure Description

[0022] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments in conjunction with the following drawings. The drawings are for illustrative purposes only and are not intended to limit the scope of this application.

[0023] Figure 1 This is a schematic diagram of the structure of the positive electrode active material in one embodiment of this application.

[0024] Figure 2 This is a schematic diagram of the structure of the positive electrode active material in another embodiment of this application.

[0025] Figure 3 This is a schematic diagram of the process for preparing a positive electrode active material according to one embodiment of this application.

[0026] Figure 4 This is a schematic diagram of a battery according to one embodiment of this application.

[0027] Figure 5 yes Figure 4 An exploded view of a battery according to one embodiment of this application is shown.

[0028] Figure 6 This is a schematic diagram of a battery module according to one embodiment of this application.

[0029] Figure 7 This is a schematic diagram of a battery pack according to one embodiment of this application.

[0030] Figure 8 yes Figure 7 An exploded view of a battery pack according to one embodiment of this application is shown.

[0031] Figure 9 This is a schematic diagram of an electrical device in which a battery is used as a power source according to one embodiment of this application.

[0032] Figure 10This is a SEM image of the positive electrode active material of Example 1 of this application.

[0033] Figure 11 The image shows the SEM image of the positive electrode active material in Comparative Example 1.

[0034] Figure 12 The image shows the XPS plot of the positive electrode active material in Example 1.

[0035] Figure 13 The image shows the XRD pattern of the positive electrode active material in Example 1.

[0036] Figure 14 The image shows the XRD pattern of the positive electrode active material in Comparative Example 1.

[0037] Explanation of reference numerals in the attached figures:

[0038] 1: Battery pack; 2: Upper casing; 3: Lower casing; 4: Battery module; 5: Battery; 51: Housing; 52: Electrode assembly; 53: Cover plate; 11: Positive electrode active material; 111: Substrate; 112: Coating layer; 113: Transition layer. Detailed Implementation

[0039] The embodiments of the technical solution of this application are described in detail below. The following embodiments are only used to illustrate the technical solution of this application more clearly, and are therefore only examples, and should not be used to limit the scope of protection of this application.

[0040] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.

[0041] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0042] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0043] Unless otherwise specified, all steps in this application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, the mention that the method may also include step (c) indicates that step (c) may be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0044] Currently, judging from market trends, battery applications are becoming increasingly widespread. Batteries are not only used in energy storage systems such as hydropower, thermal power, wind power, and solar power plants, but also extensively in electric vehicles such as electric bicycles, electric motorcycles, and electric cars, as well as in military equipment and aerospace. With the continuous expansion of battery applications, market demand is also constantly increasing.

[0045] Sodium is an abundant and widely distributed element, and its lower cost, coupled with the similarity in working principle between sodium-ion and lithium-ion batteries, have led to its increasing attention and research. Manganese-based sodium-ion batteries utilize quaternary cathode active materials, which offer advantages such as high specific capacity, good structural stability, and low cost. However, under high voltage, oxygen in the lattice of the cathode active material is easily oxidized. On one hand, the oxidized oxygen on the surface of the cathode active material readily combines to form oxygen gas; on the other hand, the oxidized oxygen on the surface of the cathode active material readily reacts with the electrolyte to produce oxygen, leading to an increase in gas production volume within the battery and a decrease in battery cycle performance.

[0046] This application proposes a positive electrode active material in which at least a portion of the substrate surface has a coating layer. On one hand, the coating layer reduces the probability of gas generation due to side reactions occurring in the substrate upon contact with the electrolyte. On the other hand, the coating layer includes perovskite, whose ABO3 structure contains oxygen vacancies. When oxygen evolution occurs in the positive electrode active material, ABO3 can capture oxygen atoms, reducing the probability of oxygen atoms on the surface of the positive electrode active material combining to form oxygen gas, thereby reducing the amount of gas generated inside the battery under high voltage and improving the battery's cycle life. The perovskite structure in the coating layer has good lattice constant matching with the Ni-Mn-Fe-X quaternary system in the substrate, which can also improve the structural stability of the positive electrode active material during battery cycling.

[0047] The positive electrode active material proposed in this application can be used in batteries, which can be used in electrical devices that use batteries as a power source or in various energy storage systems that use batteries as energy storage elements. Electrical devices can include, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.

[0048] The first aspect of this application provides a positive electrode active material 11, as referenced... Figure 1 The positive electrode active material 11 includes a substrate 111, and at least a portion of the surface of the substrate 111 has a coating layer 112; wherein, the substrate 111 includes Na. y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, 0.8≤y≤1, 0.22≤a≤0.45, 0.33≤b≤0.45, 0.2≤c≤0.35, 0<d≤0.15, a+b+c+d=1, -0.1≤δ≤1; the coating layer 112 includes perovskite, the perovskite includes ABO3, A includes one or more of Ca, La, Sr, Al, Gd, and Y, and B includes one or more of Ni, Mn, Fe, and X.

[0049] The positive electrode active material proposed in this application has a coating layer on at least a portion of its substrate surface. On one hand, the coating layer reduces the probability of gas generation due to side reactions occurring in the substrate upon contact with the electrolyte. On the other hand, the coating layer includes perovskite, whose ABO3 structure contains oxygen vacancies. When oxygen evolution occurs in the positive electrode active material, ABO3 can capture oxygen atoms, reducing the probability of oxygen atoms on the surface of the positive electrode active material combining to form oxygen gas, thereby reducing the amount of gas generated inside the battery under high voltage and improving the battery's cycle life. The perovskite structure is an excellent sodium-ion conductor with high ionic conductivity, which can increase the migration rate of sodium ions within the coating layer and improve the battery's rate performance. The substrate in the positive electrode active material is a Ni-Mn-Fe-X quaternary system, which has high stability and a lattice constant that better matches the perovskite structure, improving the structural stability of the positive electrode active material during battery cycling. In addition, the perovskite coating has high rigidity, which can slow down the volume change of the positive electrode active material during charging, reduce the probability of cracking of the positive electrode active material, and improve the cycle stability of the positive electrode active material.

[0050] In this application, the detection method for perovskite is as follows: The sample to be tested is ground finely in an agate mortar and passed through a 350-mesh sieve in a drying room or glove box. An appropriate amount of the sieved sample is placed in the center of the sample holder groove, ensuring the loose sample powder is slightly higher than the sample holder plane. A glass slide is then gently pressed against the sample surface to level it with the frame plane, and excess powder is scraped off. After sample preparation, a Brucker D8A_A25 X-ray powder diffractometer from Brucker AxS (Germany) is used to detect perovskite using CuK... α X-rays are the radiation source, and the wavelength of the X-rays is... The 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test, the XRD diffraction peaks of the sample are compared with the standard card of the XRD analysis software to confirm whether the sample still contains ABO3.

[0051] According to some embodiments of this application, X includes copper. Thus, the matrix material includes Ni, Mn, Fe, and Cu, improving the air stability of the positive electrode active material.

[0052] According to some embodiments of this application, 0.8 ≤ y ≤ 1, for example, it can be 0.8, 0.84, 0.88, 0.92, 0.96 or 1, or a range of any of the above values. This improves the specific capacity of the positive electrode active material.

[0053] According to some embodiments of this application, 0.22 ≤ a ≤ 0.45, for example, it can be 0.22, 0.26, 0.3, 0.34, 0.38, 0.42 or 0.45, or a range of any of the above values. This improves the specific capacity of the positive electrode active material.

[0054] According to some embodiments of this application, 0.33 ≤ b ≤ 0.45, for example, it can be 0.33, 0.35, 0.37, 0.39, 0.41, 0.43, or 0.45, or a range of any of the above values. This increases the specific capacity of the positive electrode active material and reduces its cost.

[0055] According to some embodiments of this application, 0.2 ≤ c ≤ 0.35, for example, it can be 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, 0.32, or 0.35, or any range of the above values. Therefore, by keeping the Fe content within the above range, the specific capacity of the positive electrode active material can be increased, and the structural stability of the positive electrode active material can also be improved.

[0056] According to some embodiments of this application, 0 < d ≤ 0.15, for example, it can be 0.01, 0.03, 0.05, 0.07, 0.09, 0.11, 0.13, or 0.15, or a range of any of the above values. Therefore, by keeping the value of d within the above range, the probability of X precipitating on the surface of the positive electrode active material to form an impurity phase can be reduced.

[0057] According to some embodiments of this application, -0.1≤δ≤1, for example, can be -0.1, -0.05, 0, 0.1, 0.3, 0.5, 0.7, 0.9 or 1, or can be a range of any of the above values.

[0058] It should be noted that due to the cycling process, oxygen in the matrix is ​​lost, which may result in the measured oxygen content in the matrix being less than 2%.

[0059] According to some embodiments of this application, reference is made to Figure 2 A transition layer 113 may also be included between the substrate 111 and the coating layer 112, the transition layer 113 comprising Na doped with ABO3. y Ni a Mn b Fe c X d O 2+δ Therefore, compared to forming the coating layer directly on the surface of the substrate, the presence of the transition layer can make the lattice constants between the substrate and the transition layer, and between the transition layer and the coating layer, more compatible. During battery cycling, this can improve the structural stability of the coating layer and reduce the risk of the coating layer falling off.

[0060] In this application, the identification of the matrix, transition layer and coating layer in the positive electrode active material can be performed by scanning electron microscopy or by elemental analysis using X-ray photoelectron spectroscopy (XPS) to verify the presence of the transition layer.

[0061] According to some embodiments of this application, the thickness ratio of the transition layer to the covering layer can be 1:(10-50). For example, it can be 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, or 1:50, or any range of the above values. Thus, the transition layer simultaneously includes element A, element B, and the material forming the matrix. The transition layer can act as a "support," reducing the volume change of the material during charging and discharging, and minimizing the impact on the electrode structure.

[0062] In this application, the test method for the thickness of the transition layer and the covering layer is as follows: XPS is used for testing, specifically, the test can be carried out in accordance with GB / T33502-2017.

[0063] According to some embodiments of this application, the thickness of the transition layer can be 1nm-6nm, for example, it can be 1nm, 2nm, 3nm, 4nm, 5nm or 6nm, or it can be any range of the above values.

[0064] According to some embodiments of this application, the thickness of the coating layer can be 10nm-60nm, for example, it can be 10nm, 20nm, 30nm, 40nm, 50nm or 60nm, or it can be any range of the above values.

[0065] Therefore, by making the transition layer thinner and the coating layer thicker, both the specific capacity and air stability of the positive electrode active material can be taken into account.

[0066] According to some embodiments of this application, the molar ratio of Na atoms to A atoms in the positive electrode active material can be 1:(0.005-0.02). For example, it can be 1:0.005, 1:0.01, 1:0.015, or 1:0.02, or any range of the above values. Therefore, by maintaining the molar ratio of Na atoms to A atoms within the above range, a uniform coating layer is formed on the surface of the substrate, improving the oxygen capture effect, reducing the volume of gas generated within the battery, and increasing the cycle life of the battery. Simultaneously, increasing the mass ratio of the substrate in the positive electrode active material increases the specific capacity of the positive electrode active material.

[0067] In this application, the molar ratio of Na atoms to A atoms is tested by inductively coupled plasma optical emission spectrometry (ICP-OES): the instrument is turned on and ignited, standard solutions of gradient concentrations are prepared, the analysis is run sequentially, the resulting spectra are viewed, and it is ensured that the spectral peaks are free from interference, the spectral lines are linear and the correlation coefficient is >0.999; then the sample after microwave digestion is tested and analyzed.

[0068] According to some embodiments of this application, in the perovskite, A includes Ca and La, and the molar ratio of Ca atoms to La atoms can be 0.25-4. For example, it can be 0.25, 0.3, 0.35, or 0.4, or any range of the above values. Therefore, since A includes Ca and La, the ionic radii of Ca and La ions are closer to those of Na ions, making it easier to form a transition layer and reducing the volume change of the positive electrode active material during charging and discharging.

[0069] In this application, the molar ratio of Ca to La can be tested by ICP-OES. Specifically, the instrument is turned on and ignited, standard solutions of gradient concentrations are prepared, and the analysis is run sequentially. The resulting spectra are checked to ensure that there is no interference in the peaks, the spectral lines are linear and the correlation coefficient is >0.999. Then, the sample after microwave digestion is tested and analyzed.

[0070] According to some embodiments of this application, the volume average particle size D of the positive electrode active material V The value 50 can range from 3μm to 10μm. For example, it can be 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, or 10μm, or any range of the above values. Therefore, the sodium ion conduction distance within the positive electrode active material is short, and there are fewer surface side reactions, which promotes the specific capacity of the positive electrode active material and improves the capacity retention rate of batteries containing it.

[0071] In this application, D v 50 refers to the particle size corresponding to a cumulative volume distribution percentage of 50%. For example, according to standard GB / T 19077-2016 / ISO 13320:2009, the particle size is determined using a laser particle size analyzer (Malvern Master Size 2000). The specific testing procedure is as follows: Take an appropriate amount of the sample to be tested (the sample concentration should be 8%-12% with sufficient light-blocking properties), add 20 ml of deionized water, and simultaneously sonicate for 5 minutes (53 kHz / 120 W) to ensure complete dispersion of the sample. Then, measure the sample according to the standard GB / T19077-2016 / ISO 13320:2009.

[0072] A second aspect of this application provides a method for preparing a positive electrode active material, comprising: mixing a positive electrode active material matrix with an A source, and performing a first sintering to cause the A source to react with at least a portion of the surface of the positive electrode active material matrix to form a coating layer comprising perovskite; the matrix comprising Na y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, with 0.8 ≤ y ≤ 1, 0.22 ≤ a ≤ 0.45, 0.33 ≤ b ≤ 0.45, 0.2 ≤ c ≤ 0.35, 0 < d ≤ 0.15, a + b + c + d = 1, and -0.1 ≤ δ ≤ 1; the perovskite includes ABO3, A includes one or more of Ca, La, Sr, Al, Gd, and Y, and B is the Na in the reaction. y Ni a Mn b Fe c X d O 2+δThe provided metallic elements include one or more of Ni, Mn, Fe, and X. Therefore, the positive electrode active material prepared by this method has a coating layer formed in situ on at least a portion of the substrate surface. On the one hand, the coating layer can reduce the probability of gas generation due to side reactions caused by contact with the electrolyte; on the other hand, the coating layer includes perovskite. The ABO3 structure of perovskite contains oxygen vacancies. When oxygen evolution occurs in the positive electrode active material, ABO3 can capture oxygen atoms, reducing the probability of oxygen atoms on the surface of the positive electrode active material combining to form oxygen gas, thereby reducing the amount of gas generated inside the battery under high voltage and improving the cycle life of the battery. The perovskite structure is an excellent sodium-ion conductor with high ionic conductivity, which can increase the migration rate of sodium ions within the coating layer and improve the rate performance of the battery. The substrate in the positive electrode active material is a Ni-Mn-Fe-X quaternary system, which has high stability and a lattice constant that is more compatible with the perovskite structure, improving the structural stability of the positive electrode active material during battery cycling. In addition, the perovskite coating has high rigidity, which can slow down the volume change of the positive electrode active material during charging, reduce the probability of cracking of the positive electrode active material, and improve the cycle stability of the positive electrode active material.

[0073] The following provides a detailed explanation of each step in this application. (Refer to...) Figure 3 The method includes:

[0074] S100: Mixing the positive electrode active material matrix with source A.

[0075] According to some embodiments of this application, the matrix of the positive electrode active material includes Na. y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, 0.8≤y≤1, 0.22≤a≤0.45, 0.33≤b≤0.45, 0.2≤c≤0.35, 0<d≤0.15, a+b+c+d=1, -0.1≤δ≤1.

[0076] According to some embodiments of this application, the method for preparing the matrix may include mixing a sodium source, a Ni source, a Mn source, an Fe source and an X source, and performing a second sintering to obtain the matrix of the positive electrode active material.

[0077] According to some embodiments of this application, the temperature of the second sintering can be 700℃-1000℃, and the time of the second sintering is 6h-15h.

[0078] As an example, the second sintering temperature can be 700℃, 750℃, 800℃, 850℃, 900℃, 950℃, or 1000℃, or a range of any of the above values. According to some specific embodiments of this application, the second sintering temperature can be 720℃-850℃.

[0079] As an example, the second sintering time can be 6h, 8h, 10h, 12h, 14h, 16h, or 18h, or a range of any of the above values. According to some specific embodiments of this application, the second sintering time can be 7h-10h.

[0080] Therefore, by keeping the temperature and time of the second sintering within the above range, the content of the matrix in the positive electrode active material is increased, thereby increasing the specific capacity of the positive electrode active material.

[0081] According to some embodiments of this application, the A source includes one or more of a calcium source and a lanthanum source. Therefore, the perovskite in the prepared positive electrode active material includes Ca and La, which is beneficial for valence state balance and improves the structural stability of the perovskite.

[0082] According to some embodiments of this application, the calcium source includes one or more of calcium oxide, calcium carbonate, calcium hydroxide, calcium nitrate, calcium chloride, and calcium sulfate.

[0083] According to some embodiments of this application, the lanthanum source includes one or more of lanthanum oxide, lanthanum hydroxide, lanthanum nitrate, and lanthanum chloride.

[0084] According to some embodiments of this application, the A source includes a calcium source and a lanthanum source, and the molar ratio of the calcium source and the lanthanum source, calculated as Ca and La, is 0.25-4. Therefore, the molar ratio of Ca atoms to La atoms in the prepared positive electrode active material is 0.25-4, which is beneficial for valence equilibrium and improves the structural stability of the perovskite.

[0085] According to some embodiments of this application, the molar ratio of the matrix (calculated as Na) to the A source is 1:1.

[0086] (0.005-0.02). Thus, while forming a uniform coating layer on the surface of the substrate, the content of the substrate in the positive electrode active material is increased, thereby reducing battery gas production and increasing the battery's energy density.

[0087] S200: The substrate and the source A are subjected to a first sintering to obtain the positive electrode active material.

[0088] According to some embodiments of this application, in this step, a first sintering process is performed to cause the A source to react with at least a portion of the surface of the positive electrode active material matrix, forming a coating layer comprising perovskite, wherein the perovskite comprises ABO3, A comprises one or more of Ca, La, Sr, Al, Gd, and Y, and B is the Na in the reaction. y Ni a Mn b Fe c X d O 2+δ The provided metallic element includes one or more of Ni, Mn, Fe, and X. Thus, through a first sintering, a perovskite structure is formed in situ on at least a portion of the surface of the substrate. This perovskite structure traps oxidized oxygen atoms on the substrate surface in situ, reducing the probability of these oxidized oxygen atoms combining to form oxygen gas, thereby reducing gas production in the battery and improving its cycle stability.

[0089] According to some embodiments of this application, the temperature of the first sintering can be 400℃-1000℃, and the time of the first sintering is 2h-24h.

[0090] As an example, the temperature of the first sintering can be 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, or 1000℃, or a range of any of the above values. According to some specific embodiments of this application, the temperature of the first sintering can be 600℃-900℃.

[0091] As an example, the first sintering time can be 2h-24h, for example, it can be 2h, 6h, 10h, 14h, 18h, 22h or 24h, or it can be a range of any of the above values. According to some specific embodiments of this application, the first sintering time can be 4h-18h.

[0092] Therefore, by keeping the temperature and time of the first sintering within the aforementioned range, a uniform coating layer is formed on the surface of the substrate, improving the oxygen capture effect, reducing gas generation in the positive electrode active material, and enhancing the cycle stability of the battery. Simultaneously, the coating layer can also reduce the risk of sodium precipitation in the substrate, improving the structural stability of the positive electrode active material.

[0093] The third aspect of this application provides a positive electrode sheet, including the positive active material provided in the first aspect of this application or the positive active material prepared by the method provided in the second aspect of this application.

[0094] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer containing the positive electrode active material.

[0095] In this application, the positive current collector can be, for example, a metal foil or a composite current collector. The metal foil can be, for example, aluminum foil. The composite current collector can include a polymer base layer and a metal layer formed on at least one side of the polymer base layer. The material of the metal layer includes, but is not limited to, aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The polymer material of the polymer base layer can be, for example, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.

[0096] In some embodiments, the positive electrode active material is the positive electrode active substance in the positive electrode film layer. In addition to the positive electrode active material, the positive electrode film layer may optionally include a conductive agent and / or a binder. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers; the binder may include at least one selected from polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), PVDF-tetrafluoroethylene-propylene terpolymer, PVDF-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.

[0097] This application does not specifically limit the preparation method of the positive electrode sheet, and it can be prepared by referring to existing methods. For example, the positive electrode slurry is coated on the positive electrode current collector, and then dried and cold-pressed to form the positive electrode sheet. The positive electrode slurry can be formed by dispersing the positive electrode active material, optional conductive agent, optional binder and other components in a solvent (e.g., N-methylpyrrolidone) and stirring evenly.

[0098] Furthermore, the positive electrode sheet of this application does not exclude other additional functional layers besides the positive electrode film layer. For example, the positive electrode sheet may also include a conductive undercoat layer (e.g., composed of a conductive agent and a binder) disposed between the positive current collector and the positive electrode film layer. As another example, the positive electrode sheet may also include a protective layer covering the surface of the positive electrode film layer.

[0099] A fourth aspect of this application provides a battery comprising the positive electrode sheet described in the third aspect of this application.

[0100] In some embodiments, the battery further includes a negative electrode, a separator, and an electrolyte. During charging and discharging, active ions move back and forth between the positive and negative electrodes, inserting and extracting. The electrolyte acts as a conductor of ions between the positive and negative electrodes. The separator, positioned between the positive and negative electrodes, prevents short circuits while allowing ions to pass through.

[0101] [Negative electrode plate]

[0102] In some embodiments, the negative electrode sheet may include a negative current collector and a negative electrode film layer disposed on at least one side of the negative current collector, the negative electrode film layer comprising a negative electrode material.

[0103] In some embodiments, the negative electrode current collector may include a metal foil or a composite current collector. The metal foil may be, for example, copper foil. The composite current collector may include a polymer substrate and a metal layer formed on at least one side of the polymer substrate. The materials of the metal layer include, but are not limited to, copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys. The polymer materials of the polymer substrate include, but are not limited to, polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).

[0104] In this application, the negative electrode material may include negative electrode active materials well known in the art for use in secondary batteries. For example, the negative electrode active material includes at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate, etc. The silicon-based material may include at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may include at least one of elemental tin, tin oxide compounds, and tin alloys.

[0105] In some embodiments, the negative electrode film layer may optionally include a binder. The binder may include, for example, at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0106] In some embodiments, the negative electrode film may optionally include a conductive agent. As an example, the conductive agent may include at least one selected from superconducting carbon, acetylene black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0107] In some embodiments, the negative electrode film layer may optionally contain other additives, such as thickeners. Specific examples of thickeners include, but are not limited to, sodium carboxymethyl cellulose (CMC-Na).

[0108] This application does not specifically limit the preparation method of the negative electrode sheet, and it can be prepared by referring to existing methods. For example, the negative electrode material, conductive agent, binder and other negative electrode components are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry; then the negative electrode slurry is coated on a negative electrode current collector, and after drying, cold pressing, etc., a negative electrode sheet is obtained.

[0109] Electrolyte

[0110] In this application, the electrolyte can be selected from existing secondary batteries. In some embodiments, the electrolyte comprises an organic solvent, a sodium salt, and optional additives. The sodium salt includes, but is not limited to, at least one selected from NaPF6, NaClO4, NaBCl4, NaSO3CF3, and Na(CH3)C6H4SO3. The organic solvents include, but are not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), methyl ethyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butyl carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), and diethyl sulfone (ESE).

[0111] In some embodiments, the additives in the electrolyte may include negative electrode film-forming additives and positive electrode film-forming additives; they may also include additives that can improve certain battery performance, such as additives that improve battery overcharge performance, additives that improve battery high-temperature or low-temperature performance, etc. As an example, the additive may include at least one of the following: vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl sulfate (DTD), propylene sulfate, vinyl sulfite (ES), 1,3-propanesulfonate lactone (PS), 1,3-propenesulfonate lactone (PST), sulfonate cyclic quaternary ammonium salts, succinic anhydride, succinic anhydride (SN), adiponitrile (AND), tris(trimethylsilane) phosphate (TMSP), and tris(trimethylsilane) borate (TMSB).

[0112] [Isolation membrane]

[0113] In this application, the separator is disposed between the positive and negative electrode plates, primarily serving to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through. This application does not impose any particular limitation on the type of separator; various porous structures well-known in the art can be used. In some embodiments, the separator material may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. Furthermore, the separator can be a single-layer film or a multi-layer composite film. When the separator is a multi-layer composite film, the materials of each layer may be the same or different.

[0114] In some embodiments, a ceramic coating and / or a metal oxide coating are also provided on the separator.

[0115] In some implementations, the positive electrode, negative electrode, and separator can be fabricated into an electrode assembly using a winding or stacking process.

[0116] This application does not impose any particular limitation on the shape of the battery; it can be cylindrical, square, or any other arbitrary shape. For example, Figure 4 The battery 5 is a square structure, which serves as an example.

[0117] In some implementations, refer to Figure 5 The outer packaging may include a housing 51 and a cover plate 53. The housing 51 may include a base plate and side plates connected to the base plate, the base plate and side plates forming a receiving cavity. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 can be placed over the opening to close the receiving cavity. A positive electrode, a negative electrode, and a separator can be formed into an electrode assembly 52 using a winding or stacking process. The electrode assembly 52 is encapsulated within the receiving cavity. Electrolyte is immersed in the electrode assembly 52. ​​The battery 5 may contain one or more electrode assemblies 52, which can be selected by those skilled in the art according to specific practical needs.

[0118] In some implementations, the batteries can be assembled into battery modules, and the number of batteries contained in a battery module can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery module.

[0119] Figure 6 This is battery module 4, used as an example. (See reference...) Figure 6 In battery module 4, multiple batteries 5 can be arranged sequentially along the length of battery module 4. Of course, they can also be arranged in any other manner. Furthermore, these multiple batteries 5 can be fixed in place using fasteners.

[0120] Optionally, the battery module 4 may also include a housing with a receiving space in which a plurality of batteries 5 are received.

[0121] In some embodiments, the battery modules described above can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be one or more, the specific number of which can be selected by those skilled in the art according to the application and capacity of the battery pack.

[0122] Figure 7 and Figure 8 This is battery pack 1 as an example. (See reference...) Figure 7 and Figure 8 The battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box includes an upper body 2 and a lower body 3, with the upper body 2 covering the lower body 3 to form a closed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.

[0123] In addition, this application also provides an electrical device, which includes at least one of the battery, battery module, or battery pack provided in this application. The battery, battery module, or battery pack can be used as a power source for the electrical device, or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0124] As the electrical equipment, batteries, battery modules, or battery packs can be selected according to their usage requirements.

[0125] Figure 9 This is an example of an electrical device. The device could be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the device's requirements for high power and high energy density batteries, a battery pack or battery module can be used.

[0126] Another example device could be a mobile phone, tablet, or laptop. These devices typically require a slim and lightweight design and can be powered by a battery.

[0127] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0128] Example 1

[0129] First, sodium source (Na2CO3), manganese source (Mn2O3), nickel source (NiO), and copper source (CuO) are mixed evenly in a certain proportion. Then, the mixture is placed in a sagger in a box furnace and sintered at 850℃ for 15 hours. After sintering, it is cooled to room temperature and then crushed to obtain the matrix NaNi. 0.3 Mn 0.3 Fe 0.3 Cu 0.1 O2.

[0130] Calcium source (CaO) and lanthanum source (La2O3) were mixed evenly in a ball mill at a molar ratio of 1:1.25 to obtain the coating material.

[0131] The coating material and the matrix were mixed uniformly using a mixing device at a Na / (Ca+La) molar ratio of 1:0.01. The mixed material was then sintered in a muffle furnace at 750℃ for 8 hours, with dry air purging during the process. After sintering, the mixture was naturally cooled to room temperature to obtain the positive electrode active material with a Ca coating layer. 0.4 La 0.6 MnO3.

[0132] Example 2

[0133] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of Na / (Ca+La) was adjusted to 1:0.005 during mixing.

[0134] Example 3

[0135] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of Na / (Ca+La) was adjusted to 1:0.004 during mixing.

[0136] Example 4

[0137] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of Na / (Ca+La) was adjusted to 1:0.02 during mixing.

[0138] Example 5

[0139] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of Na / (Ca+La) was adjusted to 1:0.03 during mixing.

[0140] Example 6

[0141] Manganese-based sodium electrochemical materials were prepared according to the method of Example 1, except that the first sintering temperature during the formation of perovskite was adjusted to 350°C.

[0142] Example 7

[0143] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the first sintering temperature during the formation of perovskite was adjusted to 400°C.

[0144] Example 8

[0145] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the first sintering temperature during the formation of perovskite was adjusted to 600°C.

[0146] Example 9

[0147] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the first sintering temperature during the formation of perovskite was adjusted to 900°C.

[0148] Example 10

[0149] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the first sintering temperature during the formation of perovskite was adjusted to 1000°C.

[0150] Example 11

[0151] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that sodium source (Na2CO3), manganese source (Mn2O3), nickel source (NiO), and zinc source (ZnO) were mixed evenly in a certain proportion, and then placed in a sagger in a box furnace and sintered at 850°C for 15 hours. After sintering, the mixture was cooled to room temperature and then crushed to obtain the matrix NaNi. 0.3 Mn 0.3 Fe 0.3 Zn 0.1 O2.

[0152] Example 12

[0153] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of calcium source (CaO) to lanthanum source (La2O3) was 1:5.

[0154] Example 13

[0155] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of calcium source (CaO) to lanthanum source (La2O3) was 1:4.

[0156] Example 14

[0157] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of calcium source (CaO) to lanthanum source (La2O3) was 1:0.25.

[0158] Example 15

[0159] Manganese-based sodium electrochemical materials were prepared according to the method in Example 1, except that the molar ratio of calcium source (CaO) to lanthanum source (La2O3) was 1:0.22.

[0160] Comparative Example 1

[0161] The matrix NaNi of Example 1 0.3 Mn 0.3 Fe 0.3 Cu 0.1 O2 is used as the positive electrode active material.

[0162] Test case

[0163] 1. Morphological characteristics

[0164] SEM testing: Field emission scanning electron microscope (Zeiss Gemini 360) was used for testing according to JY / T010-1996 standard.

[0165] 2. Crystal phase characterization

[0166] Grind the sample to be tested into a fine powder in an agate mortar and pestle in a drying room or glove box, then pass it through a 350-mesh sieve. Take an appropriate amount of the sieved sample and place it in the center of the sample holder groove, ensuring the loose sample powder is slightly higher than the sample holder plane. Gently press a glass slide onto the sample surface to level it with the frame plane, and scrape off any excess powder. After sample preparation, use a Brucker D8A_A25 X-ray powder diffractometer (Brucker AxS, Germany) with CuK... α X-rays are the radiation source, and the wavelength of the X-rays is... The 2θ angle range is 5°-60°, and the scanning rate is 4° / min. After the test is completed, the XRD diffraction peaks of the sample are compared with the standard card of the XRD analysis software to confirm whether the sample contains a perovskite structure.

[0167] 3. Elemental Analysis

[0168] The instrument standard references EPA 6010D-2014, "Inductively Coupled Plasma Atomic Emission Spectrometry". The sample is chemically treated and digested into a solution, then atomized and injected into the plasma to elicit characteristic spectral lines of the elements. The elemental content is qualitatively and quantitatively analyzed based on the wavelength and intensity of the spectral lines (which are proportional to the concentration).

[0169] 4. Gas-producing properties

[0170] The volume change of the battery after 500 cycles was tested using the water displacement method.

[0171] 5. Cyclic performance

[0172] At 25℃, after fabricating a coin cell using layered oxide cathode active material, it was charged to 4.3V at a constant current density of 10mA / g, and then discharged to 2V at a constant current density of 10mA / g, yielding the discharge specific capacity C0 of the coin cell. Subsequently, it underwent 50 charge-discharge cycles at a constant current density of 10mA / g, and the discharge specific capacity C1 of the 50th cycle was recorded. The capacity retention rate of the layered oxide cathode active material after 50 cycles is calculated as (C1 / C0) × 100%.

[0173] The button cell is prepared according to the steps shown below.

[0174] Preparation of the positive electrode sheet: The layered oxide positive electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are thoroughly mixed in an appropriate amount of solvent NMP at a mass ratio of 80:15:5 to form a uniform positive electrode slurry; the positive electrode slurry is uniformly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, it is punched into a disc with a diameter of 14mm to obtain the positive electrode sheet.

[0175] Negative electrode: Made of metallic sodium.

[0176] Preparation of electrolyte: Equal volumes of ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed to obtain an organic solvent. Then, NaClO4 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.

[0177] Separator membrane: Porous polyethylene membrane is used as the separator membrane.

[0178] Preparation of button cell: Stack the above-mentioned positive electrode, separator, and negative electrode in sequence, so that the separator is placed between the positive electrode and the negative electrode to play a role in isolation. Add the prepared electrolyte to complete the preparation of button cell.

[0179] The preparation methods of the batteries in Examples 1-15 and Comparative Example 1 are the same as those in Example 1, with the differences detailed in Table 1.

[0180] Table 1

[0181]

[0182]

[0183] The test results of the batteries in Examples 1-15 and Comparative Example 1 are shown in Table 2.

[0184] Table 2

[0185] Example 1 189 2.3 92 Example 2 186 2.5 83 Example 3 182 8.4 82 Example 4 183 2.4 91 Example 5 181 8.8 80 Example 6 183 8.0 83 Example 7 180 6.8 80 Example 8 184 2.9 90 Example 9 183 3.0 89 Example 10 176 4.0 82 Example 11 187 2.5 91 Example 12 185 4.7 85 Example 13 186 2.8 88 Example 14 183 2.7 89 Example 15 184 5.0 83 Comparative Example 1 188 9.3 76

[0186] Conclusion: Comparing Examples 1-15 with Comparative Example 1, it can be seen that the positive electrode active material proposed in this application, when used to prepare a battery, can reduce the gas production volume after battery cycling and improve the battery's cycle capacity retention. This indicates that forming a perovskite coating layer on at least a portion of the surface of the positive electrode active material can reduce the probability of gas production due to side reactions between the substrate and the electrolyte. Furthermore, the perovskite can capture oxygen atoms, reducing the probability of oxygen atoms on the surface of the positive electrode active material combining to form oxygen gas, thereby reducing the amount of gas produced inside the battery under high voltage.

[0187] As can be seen from Examples 1-5, by adjusting the molar ratio of Na / (Ca+La) in the positive electrode active material, the gas production volume after battery cycling can be reduced, and the cycle capacity retention rate of the battery can be improved. This indicates that by adjusting the molar ratio of Na / (Ca+La), a uniform coating layer can be formed on the surface of the positive electrode active material, which can improve the effect of isolating the substrate and electrolyte and improve the oxygen capture effect.

[0188] As can be seen from Examples 6-10, by adjusting the temperature during the first sintering, the gas production volume after battery cycling can be reduced, and the battery's cycle capacity retention rate can be improved. This indicates that by controlling the first sintering temperature within the protection range of this application, the uniformity of the coating layer formed on the surface of the positive electrode active material can be improved, thereby improving the effect of isolating the substrate and electrolyte and enhancing the oxygen capture capability.

[0189] As can be seen from Examples 12-15, by adjusting the molar ratio of calcium source (CaO) and lanthanum source (La2O3), the gas production volume after battery cycling can be reduced and the cycle capacity retention rate of the battery can be improved. This indicates that by adjusting the molar ratio of Ca and La, the structural stability of the coating layer can be improved, thereby improving the oxygen capture effect.

[0190] Appendix Figure 10 Here is a SEM image of the positive electrode active material of Example 1 of this application, attached. Figure 11 The image shows the SEM image of the positive electrode active material in Comparative Example 1. A comparison reveals that... Figure 10 The surface of the positive electrode active material is relatively rough and has a coating layer. Figure 11 The surface of the positive electrode active material is relatively smooth and has not formed a coating layer.

[0191] Appendix Figure 12 The XPS image of the positive electrode active material in Example 1 shows that the peak around 830 is the characteristic peak of La. The high peak intensity on the surface of the positive electrode active material indicates that there is a coating layer on the material surface. After etching for 60 nm, the coating layer has been completely etched away, but the characteristic peak of La still exists, indicating that there is a transition layer.

[0192] Appendix Figure 13 The image shows the XRD pattern of the positive electrode active material of Example 1. The spectrum contains characteristic peaks of perovskite, indicating that the positive electrode active material contains a coating layer formed by perovskite.

[0193] Appendix Figure 14 The image shows the XRD pattern of the positive electrode active material in Comparative Example 1. The spectrum does not contain characteristic peaks of perovskite, indicating that there is no perovskite in the positive electrode active material.

[0194] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application, and they should all be covered within the scope of the claims and specification of this application. In particular, as long as there is no structural conflict, the various technical features mentioned in the embodiments can be combined in any way. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. A positive electrode active material, characterized in that, Includes a substrate, at least a portion of the surface of which has a coating layer; wherein, The matrix includes Na. y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, 0.8≤y≤1, 0.22≤a≤0.45, 0.33≤b≤0.45, 0.2≤c≤0.35, 0<d≤0.15, a+b+c+d=1, -0.1≤δ≤1; The coating layer comprises perovskite, which comprises ABO3, where A comprises one or more of Ca, La, Sr, Al, Gd, and Y, and B comprises one or more of Ni, Mn, Fe, and X.

2. The positive electrode active material according to claim 1, characterized in that, A transition layer is further included between the substrate and the coating layer, the transition layer comprising Na doped with ABO3. y Ni a Mn b Fe c X d O 2+δ .

3. The positive electrode active material according to claim 2, characterized in that, The thickness ratio of the transition layer to the covering layer is 1:(10-50).

4. The positive electrode active material according to any one of claims 1-3, characterized in that, In the positive electrode active material, the molar ratio of Na atoms to A atoms is 1:(0.005-0.02).

5. The positive electrode active material according to any one of claims 1-4, characterized in that, In the perovskite, A includes Ca and La, and the molar ratio of Ca atoms to La atoms is 0.25-4.

6. The positive electrode active material according to any one of claims 1-5, characterized in that, The volume average particle size D of the positive electrode active material V 50 is 3μm-10μm.

7. A method for preparing a positive electrode active material, characterized in that, include: The positive electrode active material matrix is ​​mixed with source A and subjected to a first sintering, so that source A reacts with at least a portion of the surface of the positive electrode active material matrix to form a coating layer including perovskite. The matrix includes Na. y Ni a Mn b Fe c X d O 2+δ X includes one or more of Zn, Cu, and Co, 0.8≤y≤1, 0.22≤a≤0.45, 0.33≤b≤0.45, 0.2≤c≤0.35, 0<d≤0.15, a+b+c+d=1, -0.1≤δ≤1; The perovskite comprises ABO3, where A includes one or more of Ca, La, Sr, Al, Gd, and Y, and B is the Na in the reaction. y Ni a Mn b Fe c X d O 2+δ The provided metallic element includes one or more of Ni, Mn, Fe, and X.

8. The method according to claim 7, characterized in that, The method includes: mixing sodium source, Ni source, Mn source, Fe source and X source, and performing a second sintering to obtain the matrix of the positive electrode active material.

9. The method according to claim 7 or 8, characterized in that, The A source includes one or more of calcium and lanthanum sources.

10. The method according to claim 9, characterized in that, The calcium source includes one or more of calcium oxide, calcium carbonate, calcium hydroxide, calcium nitrate, calcium chloride, and calcium sulfate; The lanthanum source includes one or more of lanthanum oxide, lanthanum hydroxide, lanthanum nitrate, and lanthanum chloride.

11. The method according to any one of claims 7-10, characterized in that, The A source includes a calcium source and a lanthanum source, and the molar ratio of the calcium source and the lanthanum source, calculated as Ca and La, is 0.25-4.

12. The method according to any one of claims 7-11, characterized in that, The molar ratio of the matrix (calculated as Na) to the A source is 1:(0.005-0.02).

13. The method according to claim 8, characterized in that, One or more of the following conditions must be met: The first sintering temperature is 400℃-1000℃, and the first sintering time is 2h-24h; The second sintering temperature is 700℃-1000℃, and the second sintering time is 6h-15h.

14. The method according to claim 8, characterized in that, One or more of the following conditions must be met: The first sintering temperature is 600℃-900℃, and the first sintering time is 4h-18h; The second sintering temperature is 720℃-850℃, and the second sintering time is 7h-10h.

15. A positive electrode plate, characterized in that, Includes the positive electrode active material according to any one of claims 1-6 or the positive electrode active material prepared by the method according to any one of claims 7-14.

16. A battery, characterized in that, Includes the positive electrode sheet as described in claim 15.

17. An electrical appliance, characterized in that, Includes the battery as described in claim 16.

Citation Information

Patent Citations

  • Positive electrode active material, preparation method thereof and electric device

    CN115832233A

  • Positive-electrode active material and manufacturing method thereof, secondary battery, battery module, battery pack, and apparatus

    US20230119115A1